2021
DOI: 10.3390/ijms22083996
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Efficacy of Bacterial Cellulose Dressings Chemisorbed with Antiseptics against Biofilm Formed by Pathogens Isolated from Chronic Wounds

Abstract: Local administration of antiseptics is required to prevent and fight against biofilm-based infections of chronic wounds. One of the methods used for delivering antiseptics to infected wounds is the application of dressings chemisorbed with antimicrobials. Dressings made of bacterial cellulose (BC) display several features, making them suitable for such a purpose. This work aimed to compare the activity of commonly used antiseptic molecules: octenidine, polyhexanide, povidone-iodine, chlorhexidine, ethacridine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 215 publications
2
42
1
1
Order By: Relevance
“…The lowest minimal inhibitory concentrations were received for OCT, PHMB, and CHX, regardless of whether it was performed in TSB and TSB+G (Figures 5 and S6). Thus, our results agree with reports indicating high inhibitory effects of these antiseptics, even diluted several times below the working solutions [65]. As mentioned in the first part of the discussion, the supplementary glucose added to the TSB did not correlate with significantly more robust formation of S. aureus biofilm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lowest minimal inhibitory concentrations were received for OCT, PHMB, and CHX, regardless of whether it was performed in TSB and TSB+G (Figures 5 and S6). Thus, our results agree with reports indicating high inhibitory effects of these antiseptics, even diluted several times below the working solutions [65]. As mentioned in the first part of the discussion, the supplementary glucose added to the TSB did not correlate with significantly more robust formation of S. aureus biofilm.…”
Section: Discussionsupporting
confidence: 92%
“…GRAN and MICR displayed lower efficacy towards biofilms formed in DMEM than PHMB and GENTA, which did not correlate with results obtained in TSB and TSB+G. A lack of GRAN and MICR antibiofilm efficacy was confirmed also in previously reported research [18,65]. Surprisingly, MBEC values of GENTA against biofilm formed in DMEM were not obtained; moreover, application of this antibiotic led to higher biofilm eradication than application of PHMB and HOCl/NaOCl.…”
Section: Discussionmentioning
confidence: 52%
“…The relatively easy-to-perform introduction of locally active antiseptic into BC provides an additional promising avenue for chronic wound treatment. In fact, a number of studies have shown a high level of eradication of wound pathogens by antiseptic molecules released from BC, both in vitro and in vivo [ 54 , 55 , 56 , 57 , 58 ]. Further, an increasing number of such antiseptic-containing BC dressings are commercially available and applied in clinical practice [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The third disadvantage is of a strictly methodological character and concerns the methods of the pseudomonal biofilm culturing in a 96-well plate setting. As we and other teams reported earlier [ 51 , 52 , 53 , 54 , 55 ], the commonly acknowledged microtiter plate methods, although applicable for the testing of biofilms localized and firmly adhered to the bottom of the plate well (as in the case of S. aureus or C. albicans ), are of low applicability for analyses of slime-forming (and filling the whole volume of the plate well) biofilms of the Enterobacteriacae or Pseudomonas family. The subsequent procedures of rinsing and washing that are necessary to perform the crystal violet assay often lead to the random removal of the pseudomonal biofilm and to bias the results of high standard deviations.…”
Section: Discussionmentioning
confidence: 91%